Nouvelles considérations sur les Algonquins et le totémisme - Emmanuel Désveaux (Journal de la Société des Américanistes)
New considerations about Algonquian people and totemism. The recent publication of a paper which oddly attacks the general pattern imagined for the first time by Lévi-Strauss in The Totemism today provides an opportunity for a new reappraisal of the famous table of permutations which lays at the core of this book. This paper shows that the four combinations occur in the Algonquin area. This observation leads to the idea of building a full Algonquin « totemic » system, that is finaly achieved using a Klein’s group and the canonical formula of myths. The semantical outcome of these operations is a deny of substance. Various considerations follow, adressed at the regional and the continental scales.